Propuesta metodológica para la caracterización geotécnica de un suelo tropical derivado de rocas volcánicas (2019)
Introduction− Soils found in tropical zones, as they are subject to factors that favour the chemical meteorisation process, tend to have particular geotechnical properties as opposed to those found in temperate zones. Fundamental aspects such as the degree of meteorization and genesis of the material, which tend to influence soil properties, are not taken into account by the methodologies intended to study the characteristics of these soils. Consequently, they are insufficient, requiring complementary procedures for an adequate description of the geotechnical characteristics of the material. Objective− To propose a methodology for the characterization of a tropical soil derived from volcanic rocks. This is an attempt to adequately describe this type of soil and extrapolate it to soils of tropical regions derived from different rocks. For this purpose, a tropical soil located on a slope southwest of the municipality of Caldas in Antioquia (Colombia) was taken as a case study. Methodology− An experimental program was developed to evaluate the physical, chemical, mineralogical and hydro-mechanical properties of the material in the study area. Results− It was found that the relationship between the degree of weathering and the genesis of the material have an influence on the geotechnical properties evaluated. Conclusions− With this methodological proposal it was possible to evaluate important aspects such as the degree of meteorization and genesis of the material, obtaining not only basic geotechnical parameters for the analysis, design and execution of civil projects but also a better description of the material.